2013
DOI: 10.1111/2041-210x.12057
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influence on transmitter detection probability in biotelemetry: developing a general model of acoustic transmission

Abstract: Summary1. Environmental factors, such as wind, may have a strong influence on the detection probability and detection rate of acoustic telemetry tags. The effect of environmental factors may obscure biological effects and distort the interpretation of acoustic telemetry data. 2. This study was undertaken with fish internally tagged with acoustic transmitters containing depth sensors and monitored by an array of automatic receivers. The influence of environmental factors on the hourly detection rate was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 20 publications
8
110
4
Order By: Relevance
“…This detection range is in the range of previous reports, which encompass both higher (Hobday & Pincock, 2011;Huveneers et al, 2016) and similar range values (Welsh et al, 2012;Cagua et al, 2013, Stocks et al, 2014. Some other publications have reported a broad range of distances within the same study (How & de Lestang, 2012;Cagua et al, 2013;Gjelland & Hedger, 2013). Although the detection ranges differ extensively between the cited studies, they all concluded that detection range strongly depends upon meteorological and oceanographic environmental variables, on sediment characteristics and on the environment's topographic complexity factors which all influence sound propagation in water.…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 79%
See 4 more Smart Citations
“…This detection range is in the range of previous reports, which encompass both higher (Hobday & Pincock, 2011;Huveneers et al, 2016) and similar range values (Welsh et al, 2012;Cagua et al, 2013, Stocks et al, 2014. Some other publications have reported a broad range of distances within the same study (How & de Lestang, 2012;Cagua et al, 2013;Gjelland & Hedger, 2013). Although the detection ranges differ extensively between the cited studies, they all concluded that detection range strongly depends upon meteorological and oceanographic environmental variables, on sediment characteristics and on the environment's topographic complexity factors which all influence sound propagation in water.…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 79%
“…It was mainly influenced by noise and wind speed in relation to distance, the interaction between tilt and azimuth, and current speed, which is in agreement with Gjelland & Hedger (2013) and Huveneers et al (2016). In contrast, Stocks et al (2014) listed wave height as the principal factor affecting detection range.…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 73%
See 3 more Smart Citations